An Analysis of Students’ Motivation in English Language Learning at Vocational High School 5 Jambi City - Yanti Ismiyati; Ridho Praja Dinata (Universitas Batanghari Jambi, 2022)
This research aimed to determine students’ motivation in English Language Learning. Learning success depends on the motivation of high or low on students in learning. The research design in this study is mixed method. The population of this study were all 10th grade students at SMK N 5 Jambi city. The sample used is random sampling. The researcher took students in each 10th Marketing Program. The research instrument was a questionnaire and interview. Data analysis was using likert analysis, percentage formula and to strengthen research. The results of this study are indicated by students' answers in the questionnaire and interview. There are 30 questions in the questionnaire. 15 questions for intrinsic motivation and 15 questions for extrinsic motivation. The result shows that students' intrinsic motivation score is 62% and extrinsic students are 38%. This means that students at Vocational High School 5 Jambi city have intrinsic motivation that is higher than extrinsic motivation in learning English.